Contribution of the Participatory Forest Management (PFM) intervention to the socio-economic development in the Southern Cape Forests : a retrospective approach - Holmes, Tania Natasha (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2007.